The application of pomelo peel as a carrier for adsorption of epigallocatechin‐3‐gallate. (12th March 2018) - Zhang, Guoying; Sun, Yun; Guo, Yaling; Liu, Jianghong; Wu, Liangyu; Lin, Jinke
Abstract: BACKGROUND: Pomelo ( Citrus grandis ) is the largest citrus fruit, the peel of which is a well‐known agricultural wastes. Disposal of pomelo peel after consumption is a serious environment problem. As a natural, versatile bio‐absorbent, pomelo peel has shown excellent adsorption capacity for several pollutants, attributed to its micro‐pores; however, there is no relevant report on its adsorption capacity for natural products or food ingredients. The ability of pomelo peel to adsorb epigallocatechin‐3‐gallate (EGCG) was examined in this study. The physicochemical characterizations of pomelo peel were determined by Fourier transform infrared spectroscopy, scanning electron microscopy and high‐performance liquid chromatography. The adsorption process of EGCG onto pomelo peel from aqueous solution was carried out at a range of concentrations (50–800 mg L −1 ) and temperatures (25, 40 and 55 °C). RESULTS: The main components of pomelo peel are composed of dietary fiber, which provide sufficient adsorption sites during the adsorption process. The adsorption of EGCG onto pomelo peel showed excellent fitness with a pseudo‐second‐order model. Both Langmuir and Freundlich models were able to describe the isothermal adsorption of EGCG onto pomelo peel. The results of thermodynamic analysis suggested that adsorption is spontaneous and endothermic in nature, and that the process is likely to be dominated by a physisorption mechanism. CONCLUSION: The results of this study indicate that pomelo peel has potential adsorption capacity for EGCG, which can be used as an effective, low‐cost carrier for delivery of natural products in functional food and dietary supplement applications. © 2018 Society of Chemical Industry